THE KMS CONDITION AND PASSIVE STATES - Batty, C (1982)
Any state which is passive for a C*-dynamical system (A, R, α), and ergodic for a system (A, G, γ), where α and γ commute, is KMS at some temperature. Any state which is passive for (A, R, α) and central for (A, G, γ) is approximable by convex combinations of KMS states at different temperatures. © 1982.